Pengaruh Promosi, Brand Ambasador, Dan Brand Image terhadap Minat Beli UMKM Bebek Bumbu Ijo Buk Fenny di Kota Mataram - Imelda Linda Wiraguna; Stevany Hanalyna Dethan; Baiq Nadia Nirwana; L. Jatmiko Jati; Susilo Talidobel (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
One of the MSMEs in the culinary field in the city of Mataram is Bebek Bumbu Ijo Buk Fenny which focuses on Indonesian cuisine, facing the challenge of continuing to maintain and increase consumer buying interest amid the many similar culinary choices. Bebek Bumbu Ijo Buk Fenny has used its brand ambassador to introduce its products to a wide audience. However, there are challenges in maintaining a consistent brand image. The purpose of this study was to determine and analyze the influence of promotion, brand ambassador, and brand image on the buying interest of MSME consumers Bebek Bumbu ijo Buk Fenny. This study uses a quantitative approach with SPSS data Analysis tool and the population in this study is not known so that it uses 100 respondents and data collection techniques using questionnaires in the form of google form. The results of this study that the variable promotion (X1) has a positive and significant effect on buying interest (Y). brand ambassador variable (X2) has a positive and significant effect on buying interest (Y). Brand image variable (X3) has a positive and significant effect on buying interest (Y). Simultaneous test results proved that the variable promotion (X1), brand ambassador (X2), and brand image (X3) simultaneously and significantly affect the variable buying interest(Y).